Assessment of cytotoxicity, genotoxicity and 7-ethoxyresorufin-O-deethylase (EROD) induction in sediment extracts from New Zealand urban estuaries - Heinrich, Patrick; Petschick, Lara L.; Braunbeck, Thomas (Ecotoxicology, 2017)
Sediments represent a major sink for contaminants resulting from industrial and agricultural activities - especially lipophilic substances. This study exclusively used in vitro methodologies to characterize specific toxicity effects of contaminants in sediment extracts from two urban New Zealand estuaries. Sediment extracts were prepared and tested for a range of biological endpoints. The micronucleus and comet assays in V79 cells were used to assess genotoxicity. Induction of 7-ethoxyresorufin-O-deethylase in piscine RTL-W1 cells was determined to estimate dioxin-like toxicity. Cytotoxic potentials were analyzed by neutral red uptake and MTT reduction. There was evidence of strong dioxin-like toxicity and moderate cytotoxicity. Genotoxicity was distinct in the micronucleus assay, but low in the comet assay. The results indicate the presence of chemicals in the sediments with the potential to pose a risk through multiple mechanisms of toxicity, the identities and amounts of which will be disclosed in a parallel study alongside with in vivo toxicity data.